Solid electrolyte ceramics and solid-state batteries

By using solid electrolyte ceramics with a garnet-type crystal structure in solid-state batteries and adding an appropriate amount of transition metal elements to adjust the content of La and transition metal elements, the problem of increasing electron conductivity caused by the generation of Li-Bi-O compounds in traditional solid-state batteries is solved, and a high-efficiency balance between ionic conductivity and low electron conductivity is achieved.

JP7666518B2Active Publication Date: 2025-04-22MURATA MFG CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2022563798
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-11-17
Filing Date
2021-11-17
Publication Date
2025-04-22
Estimated Expiration
2041-11-17

AI Technical Summary

Technical Problem

In traditional solid-state batteries, garnet solid-state electrolyte ceramics are prone to generate Li-Bi-O compounds during use, resulting in an increase in electron conductivity and short circuit or leakage current problems.

Method used

A solid electrolyte ceramic with a garnet-type crystal structure is used, including Li, La and O, and one or more transition metal elements such as Co, Ni, Mn and Fe are added. By adjusting the content of La and the total content of transition metal elements, a specific relational equation is satisfied to suppress the increase of electron conductivity.

Benefits of technology

It realizes that high ion conductivity is maintained during the operation of solid-state battery, while effectively suppressing the increase in electronic conductivity and avoiding the problems of short circuit and leakage current.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007666518000001
    Figure 0007666518000001
  • Figure 0007666518000002
    Figure 0007666518000002
  • Figure 0007666518000003
    Figure 0007666518000003
Patent Text Reader

Abstract

The present invention provides solid electrolyte ceramics that more sufficiently suppress an increase in the electron conductance resulting from operation of a solid-state battery while still having excellent ion conductivity. The present invention provides solid electrolyte ceramics that contain at least Li (lithium), La (lanthanum), and O (oxygen), that further contain at least one type of transition metal elements selected from the group consisting of Co (cobalt), Ni (nickel), Mn (manganese), and Fe (iron), and that have a garnet crystal structure. When the content of the La is X (mol%) and the total content of the at least one type of transition metal elements is Y (mol%), the solid electrolyte ceramics satisfy any one of three relational expressions (1) to (3): (1) 0.01 ≤ Y ≤ 6.0 in the range of 147.5 < X < 150.0; (2) 0.01 ≤ Y ≤ 9.0 in the range of 145.0 < X ≤ 147.5; and (3) 0.01 ≤ Y ≤ 12.0 in the range of 132.0 ≤ X ≤ 145.0.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a solid electrolyte ceramic and a solid-state battery including the solid electrolyte ceramic. [Background technology]

[0002] In recent years, the demand for batteries as power sources for portable electronic devices such as mobile phones and portable personal computers has expanded significantly. As batteries for such applications, development of sintered solid-state secondary batteries (so-called "solid-state batteries") that use a solid electrolyte as the electrolyte and whose other components are also composed of solids is underway.

[0003] A solid-state battery includes a positive electrode layer, a negative electrode layer, and a solid electrolyte layer laminated between the positive electrode layer and the negative electrode layer. In particular, the solid electrolyte layer includes a solid electrolyte ceramic, and is responsible for ion conduction between the positive electrode layer and the negative electrode layer. Solid electrolyte ceramics are required to have higher ionic conductivity and lower electronic conductivity. As such solid electrolyte ceramics, attempts have been made to use ceramics obtained by sintering a garnet-type solid electrolyte substituted with Bi from the viewpoint of higher ionic conductivity (for example, Patent Document 1 and Non-Patent Document 1). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2015-050071 A [Non-patent literature]

[0005] [Non-Patent Document 1] Gao et al., SolidState Ionics, 181 (2010) 1415-1419 Summary of the Invention [Problem to be solved by the invention]

[0006] The inventors of the present invention have found that the following problems occur in solid-state batteries using the above-mentioned conventional solid electrolyte ceramics. In particular, in conventional solid-state batteries using garnet-type solid electrolyte ceramics containing Bi, impurities such as Li-Bi-O-based compounds are easily generated at grain boundaries, and these Li-Bi-O-based compounds are reduced during operation of the solid-state battery (i.e., during charging and discharging), increasing the electronic conductivity. When the electronic conductivity increases, the solid-state battery may short-circuit and / or the leakage current may increase.

[0007] The inventors of the present invention also found that the inclusion of a transition metal element such as Co is effective in suppressing the formation of Li-Bi-O based compounds, but also found that the following new problem occurs: In detail, when a relatively large amount of a transition metal element is included, impurities containing transition metals such as Li-La-Co-O based compounds different from Li-Bi-O based compounds are formed, and these impurities also increase the electronic conductivity during operation of the solid-state battery.

[0008] An object of the present invention is to provide a solid electrolyte ceramic that has excellent ionic conductivity and that more sufficiently suppresses an increase in electronic conductivity due to the operation of a solid-state battery.

[0009] Another object of the present invention is to provide a solid electrolyte ceramic that has excellent ionic conductivity even when a relatively large amount of a transition metal element is contained, and that more sufficiently suppresses an increase in electronic conductivity due to the operation of a solid-state battery. [Means for solving the problem]

[0010] The present invention relates to A solid electrolyte ceramic having a garnet-type crystal structure, which contains at least Li (lithium), La (lanthanum), and O (oxygen), and further contains one or more transition metal elements selected from the group consisting of Co (cobalt), Ni (nickel), Mn (manganese), and Fe (iron), The solid electrolyte ceramic has the following general formula (I): [Chemical formula] (In formula (I), A is one or more elements selected from the group consisting of Li (lithium), Ga (gallium), Al (aluminum), Mg (magnesium), Zn (zinc), and Sc (scandium), and contains at least Li (lithium); B is one or more elements selected from the group consisting of La (lanthanum), Ca (calcium), Sr (strontium), Ba (barium), and lanthanoid elements, and contains at least La (lanthanum); D is one or more elements selected from the group consisting of transition elements capable of six-coordinating with oxygen and typical elements belonging to Groups 12 to 15; α satisfies 5.0 ≤ α ≤ 8.0; β satisfies 2.5 ≤ β ≤ 3.5; γ satisfies 1.5 ≤ γ ≤ 2.5; ω satisfies 11 ≤ ω ≤ 13) having a chemical composition represented by Regarding solid electrolyte ceramics, when the content of D is 100 mol%, and the content of La is X (mol%) and the total content of the one or more transition metal elements is Y (mol%), it satisfies any one of the following relational expressions (1) to (3): (1) 0.01 ≤ Y ≤ 6.0 in the range of 147.5 < X < 150.0; (2) 0.01 ≤ Y ≤ 9.0 in the range of 145.0 < X ≤ 147.5; (3) 0.01 ≤ Y ≤ 12.0 in the range of 132.0 ≤ X ≤ 145.0. [Advantages of the Invention]

[0011] The solid electrolyte ceramics of the present invention have excellent ionic conductivity and more sufficiently suppress the increase in electronic conductivity due to the operation of a solid battery. [Modes for Carrying Out the Invention]

[0012] [Solid Electrolyte Ceramics] The solid electrolyte ceramic of the present invention is composed of a sintered body obtained by sintering solid electrolyte particles. The solid electrolyte ceramic of the present invention is a solid electrolyte ceramic containing at least Li (lithium), La (lanthanum) O (oxygen) and having a garnet-type crystal structure, and further containing one or more transition metal elements selected from the group consisting of Co (cobalt), Ni (nickel), Mn (manganese) and Fe (iron) (hereinafter, simply referred to as "predetermined transition metal elements"). Furthermore, the solid electrolyte ceramic of the present invention is a ceramic made of a solid electrolyte having a garnet-type crystal structure, and may contain other composite oxides or single oxides within a range that does not impair the effects of the present invention. Furthermore, from the viewpoint of better ion conductivity, it is preferable to contain Bi (bismuth). Also, it is sufficient that at least the sintered particles contained in the solid electrolyte ceramic, which is the main component of the present invention, have a garnet-type crystal structure.

[0013] The solid electrolyte ceramic of the present invention preferably has a chemical composition represented by the following general formula (I) and further contains a predetermined transition metal element.

[0014] [ka]

[0015] In formula (I), A is one or more elements selected from the group consisting of Li (lithium), Ga (gallium), Al (aluminum), Mg (magnesium), Zn (zinc) and Sc (scandium), and includes at least Li. B is one or more elements selected from the group consisting of La (lanthanum), Ca (calcium), Sr (strontium), Ba (barium), and lanthanoid elements, including at least La. Examples of lanthanoid elements include Ce (cerium), Pr (praseodymium), Nd (neodymium), Pm (promethium), Sm (samarium), Eu (europium), Gd (gadolinium), Tb (terbium), Dy (dysprosium), Ho (holminium), Er (erbium), Tm (thulium), Yb (ytterbium), and Lu (lutetium). D represents one or more elements selected from the group consisting of transition elements capable of forming 6-coordination with oxygen and typical elements belonging to groups 12 to 15. Examples of transition elements capable of forming 6-coordination with oxygen include Sc (scandium), Zr (zirconium), Ti (titanium), Ta (tantalum), Nb (niobium), Hf (hafnium), Mo (molybdenum), W (tungsten), and Te (tellurium). Examples of typical elements belonging to groups 12 to 15 include In (indium), Ge (germanium), Sn (tin), Pb (lead), Sb (antimony), and Bi (bismuth). It is preferable that D contains at least Bi from the viewpoint of more excellent ion conductivity and more sufficient suppression of the increase in electronic conductivity during operation.

[0016] In formula (I), α, β, γ, and ω satisfy the following relations: 5.0≦α≦8.0, 2.5≦β≦3.5, 1.5≦γ≦2.5, and 11≦ω≦13, respectively. From the viewpoint of better ion conductivity and more sufficient suppression of an increase in electronic conductivity during operation, α preferably satisfies 6.0≦α≦7.0, more preferably 6.0≦α≦6.6, and further preferably 6.25≦α≦6.55. From the viewpoint of better ion conductivity and more sufficient suppression of an increase in electronic conductivity during operation, β preferably satisfies 2.65≦β≦3.30, more preferably 2.92≦β≦3.10, and further preferably 2.96≦β≦3.00. From the viewpoint of superior ionic conductivity and more sufficient suppression of an increase in electronic conductivity during operation, γ preferably satisfies 1.8≦γ≦2.5, more preferably 1.8≦γ≦2.3, and further preferably 1.9≦γ≦2.3. From the viewpoint of achieving better ion conductivity and more sufficient suppression of an increase in electronic conductivity during operation, ω preferably satisfies 11≦ω≦12.5, and more preferably satisfies 11.5≦ω≦12.5.

[0017] In the solid electrolyte ceramic of the present invention, the La deficiency in a specific range allows the solid electrolyte ceramic to have excellent ionic conductivity and to more sufficiently suppress an increase in electronic conductivity even when it contains a relatively large amount of transition metal elements. Although the details of the mechanism by which such an effect is obtained by the La deficiency in a specific range are unclear, one factor is thought to be that the La deficiency reduces the La activity in the solid electrolyte ceramic as a whole, thereby suppressing the generation of impurities containing transition metals such as Li-La-Co-O-based compounds. La deficiency means that a part of the site originally occupied by La in the garnet-type crystal structure (i.e., the La site) becomes a vacancy, or another metal element (for example, B in the general formula (II) described later) is occupied by La. 1 ) or a composite embodiment of both. In the composite embodiment, more specifically, the La site includes a site that is a vacancy and a site that is substituted with another metal element. In the solid electrolyte ceramic of the present invention, if the La content is too low, sufficient ion conductivity cannot be obtained. If the La content is too high, the increase in electronic conductivity cannot be sufficiently suppressed.

[0018] In the present invention, the La content and the content of a predetermined transition metal element in the solid electrolyte ceramics are specifically as follows. That is, when the content of D in the general formula (I) representing the chemical composition of the solid electrolyte ceramics of the present invention is 100 mol%, the La content is X (mol%), and the total content of the predetermined transition metal element is Y (mol%), the solid electrolyte ceramics of the present invention satisfy any one of the following relational expressions (1) to (3): (1) When 147.5 < X < 150.0 (especially 148.0 ≤ X ≤ 149.8), 0.01 ≤ Y ≤ 6.0 (a composite range of 0.01 ≤ Y < 2.0 and 2.0 ≤ Y ≤ 6.0) (from the viewpoints of more excellent ionic conductivity and more sufficient suppression of the increase in electronic conductivity during operation, preferably 0.01 ≤ Y ≤ 5.5 (a composite range of 0.01 ≤ Y < 2.0 and 2.0 ≤ Y ≤ 5.5), more preferably 0.03 ≤ Y ≤ 5 (a composite range of 0.03 ≤ Y < 2.5 and 2.5 ≤ Y ≤ 5.0)); (2) When 145.0 < X ≤ 147.5 (especially 146.0 ≤ X ≤ 147.5), 0.01 ≤ Y ≤ 9.0 (a composite range of 0.01 ≤ Y < 2.0 and 2.0 ≤ Y ≤ 9.0) (from the viewpoints of more excellent ionic conductivity and more sufficient suppression of the increase in electronic conductivity during operation, preferably 0.01 ≤ Y ≤ 8.0 (a composite range of 0.01 ≤ Y < 2.2 and 2.2 ≤ Y ≤ 8.0), more preferably 0.03 ≤ Y ≤ 7.5 (a composite range of 0.03 ≤ Y < 2.5 and 2.5 ≤ Y ≤ 7.5)); (3) When 132.0 ≤ X ≤ 145.0 (especially 135.0 ≤ X ≤ 145.0), 0.01 ≤ Y ≤ 12.0 (a composite range of 0.01 ≤ Y < 2.0 and 2.0 ≤ Y ≤ 12.0) (from the viewpoints of more excellent ionic conductivity and more sufficient suppression of the increase in electronic conductivity during operation, preferably 0.01 ≤ Y ≤ 11.0 (a composite range of 0.01 ≤ Y < 2.2 and 2.2 ≤ Y ≤ 11.0), more preferably 0.03 ≤ Y ≤ 10.0 (a composite range of 0.03 ≤ Y < 2.5 and 2.5 ≤ Y ≤ 10.0)). In each of the relational expressions (1) to (3), if the total content Y of the predetermined transition metal element is too much more than a predetermined value, the increase in electronic conductivity cannot be sufficiently suppressed.

[0019] The La content X and the total content Y of the predetermined transition metal elements are expressed as a ratio (mol%) when the D content is 100 mol%, but they can also be expressed as a ratio (mol%) when the number of 6-coordinated sites in the garnet-type crystal structure is 100 mol%. For example, in the case of the chemical composition of the general formula (II) described later, the ratio is 1 The total number of the 6-coordinated sites is 100 mol %. In another specific example, the 6-coordinated sites of the garnet-type crystal structure are, for example, Li5La3Nb2O 12 (ICDD Card No. 00-045-0109), the site occupied by Nb, also in the garnet-type crystal structure Li7La3Zr2O 12 This refers to the site occupied by Zr in (ICDD Card. No. 01-078-6708).

[0020] The La content and the content of a specific transition metal element can be measured by performing inductively coupled plasma (ICP) emission spectroscopy (ICP analysis) on the solid electrolyte ceramic to obtain the average chemical composition of the material. In detail, the average chemical composition is obtained based on the ICP analysis, and the La content and the Co, Mn, Ni and Fe contents can be obtained from the average chemical composition as a percentage when the content of D in the general formula (I) is taken as 100 mol %. For example, the number of 6-coordinate sites in the garnet-type crystal structure (for example, the number of Bi and D in the general formula (II) described later) can be calculated. 1 The total number of the above (the total number of the above) can be taken as 100 mol %. It is also possible to measure and calculate the amount of the above by using an X-ray photoelectron spectroscopy (XPS).

[0021] The content of Bi (bismuth) is usually 50 mol% or less when the content of D is 100 mol%, and from the viewpoint of better ion conductivity and more sufficient suppression of an increase in electronic conductivity during operation, the content of Bi is preferably more than 0 mol% and 35 mol% or less, more preferably 0.5 mol% or more and 20 mol% or less, even more preferably 2.5 mol% or more and 17.5 mol% or less, and particularly preferably 10 mol% or more and 17.5 mol% or less.

[0022] The Bi content can be measured by performing inductively coupled plasma (ICP) emission spectroscopy (ICP analysis) of the solid electrolyte ceramic to obtain the average chemical composition of the material, in the same manner as the content of a specific transition metal element. In detail, the average chemical composition is obtained based on the ICP analysis, and the Bi content is calculated based on the average chemical composition by subtracting the D content in the general formula (I) (for example, the Bi and D content in the general formula (II) described later). 1 The total number of the above (the total number of the above) can be taken as 100 mol %. It is also possible to measure and calculate the amount of the above by using an X-ray photoelectron spectroscopy (XPS).

[0023] From the viewpoint of superior ionic conductivity and more sufficient suppression of an increase in electronic conductivity during operation, the solid electrolyte ceramic of the present invention preferably satisfies the above relational formula (1) or (2), and more preferably satisfies the above relational formula (1).

[0024] The form of existence (or the form of inclusion) of the predetermined transition metal element in the solid electrolyte ceramic of the present invention is not particularly limited, and it may be present in the crystal lattice or may be present outside the crystal lattice. For example, the predetermined transition metal element may be present in the bulk, in the grain boundary, or both in the solid electrolyte ceramic. The presence of the predetermined transition metal element in the bulk means that the predetermined transition metal element is present in the metal site (lattice site) constituting the garnet-type crystal structure in the solid electrolyte ceramic of the present invention. The metal site may be any metal site, for example, Li site, La site, Bi site, or two or more of these sites. The presence of the predetermined transition metal element in the grain boundary means that the solid electrolyte ceramic of the present invention is composed of a plurality of sintered particles, and the predetermined transition metal element may be present in the interface between two or more sintered particles.

[0025] When the solid electrolyte ceramic of the present invention contains Bi, the form of existence (or the form of inclusion) of Bi (bismuth) in the solid electrolyte ceramic of the present invention is not particularly limited, and for example, the specified Bi (bismuth) may be present in the bulk, in the grain boundary, or in both in the solid electrolyte ceramic. From the viewpoint of insulation, it is preferable that Bi is present in the bulk. As an example of Bi being present in the bulk, in the solid electrolyte ceramic of the present invention, Bi may be present in the metal site (lattice site) constituting the garnet-type crystal structure.

[0026] In the present invention, the specified transition metal and / or Bi (bismuth) may be contained in a ceramic having a garnet-type crystal structure. Furthermore, the specified transition metal and / or Bi (bismuth) may be present as a composite oxide and / or a single oxide containing the specified transition metal and / or Bi (bismuth) and / or an element constituting the garnet-type solid electrolyte of the present invention. The oxide may be present at the interface between crystal grains of the ceramic having a garnet-type crystal structure, which is the main component of the present invention.

[0027] In the solid electrolyte ceramics of the present invention, Li (lithium) and La (lanthanum) may be present in the bulk, and more specifically, in the solid electrolyte ceramics of the present invention, they may be present in the Li site and La site as metal sites (lattice sites) constituting the garnet-type crystal structure, for example. In this case, Li (lithium) and La (lanthanum) may be present in part in the grain boundary, either independently or as a composite oxide.

[0028] From the viewpoint of superior ionic conductivity and more sufficient suppression of an increase in electronic conductivity during operation, the transition metal element contained in the solid electrolyte ceramic of the present invention is preferably selected from the group consisting of Co, Ni and Mn, more preferably selected from the group consisting of Co and Mn, and further preferably contains Co.

[0029] In the present invention, the solid electrolyte ceramics having a garnet-type crystal structure means that the solid electrolyte ceramics not only have a "garnet-type crystal structure" but also have a "garnet-like crystal structure". Specifically, the solid electrolyte ceramics of the present invention have a crystal structure that can be recognized as a garnet-type or garnet-like crystal structure by a person skilled in the field of solid batteries in X-ray diffraction. More specifically, the solid electrolyte ceramics of the present invention may show one or more main peaks corresponding to Miller indices specific to the so-called garnet-type crystal structure diffraction pattern (ICDD Card No. 422259) at a predetermined incidence angle in X-ray diffraction, or may show one or more main peaks having different incidence angles (i.e., peak positions or diffraction angles) and intensity ratios (i.e., peak intensities or diffraction intensity ratios) due to differences in composition from one or more main peaks corresponding to Miller indices specific to the so-called garnet-type crystal structure as a garnet-like crystal structure. Representative diffraction patterns of garnet-like crystal structures include, for example, ICDD Card No. 00-045-0109.

[0030] As a specific embodiment, the solid electrolyte ceramic of the present invention can have a chemical composition represented by general formula (II). More specifically, the solid electrolyte ceramic can have a chemical composition represented by the general formula (II) as a whole. In this case, the solid electrolyte ceramic of the present invention has the chemical composition represented by the general formula (II) and further contains a predetermined transition metal element as described above.

[0031] [ka]

[0032] In formula (II), A 1 A refers to a metallic element that occupies the Li site in the garnet-type crystal structure. 1 is an element corresponding to A in the general formula (I) and may be one or more elements selected from the group consisting of elements other than Li among the elements exemplified as A. 1 is usually one or more elements selected from the group consisting of Ga (gallium), Al (aluminum), Mg (magnesium), Zn (zinc) and Sc (scandium). 1 is preferably one or more elements selected from the group consisting of Ga (gallium) and Al (aluminum), and more preferably two elements, Ga and Al, from the viewpoints of better ionic conductivity and more sufficient suppression of an increase in electronic conductivity during operation.

[0033] In formula (II), B 1 indicates a metal element that occupies the La site in the garnet-type crystal structure. 1 is an element corresponding to B in the general formula (I) and may be one or more elements selected from the group consisting of elements other than La among the elements exemplified as B. 1 is usually one or more elements selected from the group consisting of Ca (calcium), Sr (strontium), Ba (barium), and the lanthanide elements.

[0034] In formula (II), D 1 represents a metal element occupying a 6 - coordinate site in the garnet - type crystal structure (the site occupied by Zr in the garnet - type crystal structure Li7La3Zr2O 12 (ICDD Card.No01 - 078 - 6708)). D 1 is an element corresponding to D in the general formula (I), and may be one or more elements selected from the group consisting of elements other than Bi among the same elements as those exemplified for the said D. D 1 is usually one or more elements selected from the group consisting of Zr (zirconium), Hf (hafnium), Ta (tantalum), Nb (niobium), Mo (molybdenum), W (tungsten), and Te (tellurium). From the viewpoints of more excellent ionic conductivity and more sufficient suppression of the increase in electronic conductivity during operation, it preferably contains one or more elements selected from the group consisting of Zr (zirconium) and Ta (tantalum), and more preferably contains Zr (zirconium) and Ta (tantalum).

[0035] In formula (II), x satisfies 0 < x ≤ 1.00. From the viewpoints of more excellent ionic conductivity and more sufficient suppression of the increase in electronic conductivity during operation, preferably 0.01 ≤ x ≤ 0.70, more preferably 0.02 ≤ x ≤ 0.60, still more preferably 0.05 ≤ x ≤ 0.50, particularly preferably 0.10 ≤ x ≤ 0.45, and most preferably 0.20 ≤ x ≤ 0.40. y satisfies 0 ≤ y ≤ 0.50. From the viewpoints of more excellent ionic conductivity and more sufficient suppression of the increase in electronic conductivity during operation, preferably 0 ≤ y ≤ 0.40, more preferably 0 ≤ y ≤ 0.30, still more preferably 0 ≤ y ≤ 0.20, and particularly preferably y = 0. z satisfies 0 ≤ z ≤ 2.00. From the viewpoints of more excellent ionic conductivity and more sufficient suppression of the increase in electronic conductivity during operation, preferably 0 ≤ z ≤ 0.35, more preferably 0 ≤ z ≤ 0.08, and still more preferably 0 ≤ z ≤ 0.04. γ satisfies 1.5≦γ≦2.5, and from the viewpoint of better ionic conductivity and more sufficient suppression of an increase in electronic conductivity during operation, preferably satisfies 1.8≦γ≦2.5, more preferably 1.8≦γ≦2.3, and even more preferably 1.9≦γ≦2.3.

[0036] In formula (II), p usually satisfies 6.0≦p≦7.0, and from the viewpoints of better ionic conductivity and more sufficient suppression of an increase in electronic conductivity during operation, preferably satisfies 6.0≦p≦6.6, and more preferably 6.25≦p≦6.55. a is A 1 is the average valence of A 1 The average valence of A 1 For example, if there are n1 elements X with a valence of a+, n2 elements Y with a valence of b+, and n3 elements Z with a valence of c+, then the value is expressed as (n1×a+n2×b+n3×c) / (n1+n2+n3). b is B 1 is the average valence of B 1 The average valence of B 1 For example, when n1 element X having a valence of a+, n2 element Y having a valence of b+, and n3 element Z having a valence of c+ are recognized, the above-mentioned A 1 This is the same value as the average valence of. c is D 1 is the average valence of D 1 The average valence of D 1 For example, when n1 element X having a valence of a+, n2 element Y having a valence of b+, and n3 element Z having a valence of c+ are recognized, the above-mentioned A 1 This is the same value as the average valence of.

[0037] In formula (II), q corresponds to 0.02×X for the above-described X, and usually satisfies 2.64≦q<3.00, particularly 2.70≦q≦2.996. From the viewpoint of more excellent ionic conductivity and more sufficient suppression of the increase in electronic conductivity during operation, it preferably satisfies the range converted from the range of X in the above-described relational expressions (1) and (2), and more preferably satisfies the range converted from the range of X in the above-described relational expression (1). The range converted from the range of X in the above-described relational expression means the range of q calculated by multiplying the range of X by 0.02. For example, the range converted from 147.5<X<150.0 in relational expression (1) is 2.95<p<3.00. δ represents the amount of oxygen deficiency and may be 0. δ usually only needs to satisfy 0≦δ<1. Since the amount of oxygen deficiency δ cannot be quantitatively analyzed even using the latest equipment, it may be considered to be 0. Note that the molar ratio of each element in the chemical composition of the solid electrolyte ceramics of the present invention does not necessarily coincide with the molar ratio of each element in formula (II), for example. Depending on the analysis method, there is a tendency to deviate more therefrom, but the effects of the present invention can be achieved as long as the composition deviation is not such that the characteristics change.

[0038] In the present invention, the chemical composition of the solid electrolyte ceramics may be the composition of the entire ceramic material determined using ICP (inductively coupled plasma method). Further, the chemical composition may be measured and calculated using XPS analysis, or may be determined using TEM-EDX (energy dispersive X-ray spectroscopy) and / or WDX (wavelength dispersive X-ray spectroscopy). Furthermore, the chemical composition may be obtained by performing quantitative analysis (composition analysis) at any 100 points of each of any 100 sintered particles and calculating their average values.

[0039] The content of a predetermined transition metal element (that is, Co, Ni, Mn, Fe) in the solid electrolyte ceramic of the present invention [for example, the content of D in the general formula (I) (or Bi and D in the general formula (II)) 1The molar ratio when the total number of the elements (moles) is taken as 100 mol % may be calculated by the following method. In the present invention, the chemical composition of the solid electrolyte ceramic can be determined by ICP analysis (inductively coupled plasma method), LA-ICP-MS (laser ablation ICP mass spectrometry) analysis, etc. Also, it may be measured and calculated by XPS analysis, or TEM-EDX (energy dispersive X-ray spectrometry) or WDX (wavelength dispersive X-ray spectrometry). Furthermore, the chemical composition may be obtained by quantitatively analyzing (compositionally analyzing) any 100 points of each of any 100 sintered particles and calculating the average value.

[0040] For example, the analysis by EDX or WDX measures the cross section of the solid-state battery. The cross section of the solid-state battery is a cross section parallel to the lamination direction of the positive electrode layer, the solid electrolyte layer, and the negative electrode layer. The cross section of the solid-state battery can be exposed by embedding the solid-state battery in resin and then polishing it. There is no particular limitation on the method of polishing the cross section, but the solid electrolyte layer can be exposed by cutting it with a dicer or the like and then polishing it with abrasive paper, chemical mechanical polishing, ion milling, or the like. The molar ratios of Co, Ni, Mn, and Fe to D can be calculated by quantitatively analyzing 30 the exposed cross section (solid electrolyte layer) with EDX or WDX (wavelength dispersive X-ray fluorescence analyzer).

[0041] In addition, for example, in the TEM-EELS measurement, the electrode layer or solid electrolyte layer of the solid battery is exfoliated using a FIB (focused ion beam) or the like, and then the solid electrolyte portion is measured by TEM-EELS (transmission electron microscope-electron energy loss spectroscopy: Electron Energy-Loss Spectroscopy) to detect the elements Co, Ni, Mn, and Fe contained in D in the general formula (I) and calculate the molar ratios of Co, Ni, Mn, and Fe to the content of D.

[0042] Specific examples of the chemical composition of the solid electrolyte ceramic of the present invention include the following chemical compositions. In the chemical compositions shown below, the transition metal element following the hyphen (-) may be present in the bulk and / or grain boundaries, as described above. Li 6.3 La 2.7 Zr 1.3 Ta 0.4 Bi 0.3 O 12 -Co 0.05 Li 6.3 La 2.7 Zr 1.3 Ta 0.4 Bi 0.3 O 12 -Co 0.1 Li 6.3 La 2.7 Zr 1.3 Ta 0.4 Bi 0.3 O 12 -Co 0.15 Li 6.3 La 2.7 Zr 1.3 Ta 0.4 Bi 0.3 O 12 -Co 0.2 Li 6.3 La 2.8 Zr 1.3 Ta 0.4 Bi 0.3 O 12 -Co 0.05 Li 6.3 La 2.8 Zr 1.3 Ta 0.4 Bi 0.3 O 12 -Co 0.1 Li 6.3 La 2.8 Zr 1.3 Ta 0.4 Bi 0.3 O 12 -Co 0.15 Li 6.3 La 2.8 Zr 1.3 Ta0.4 Bi 0.3 O 12 -Co 0.2 Li 6.3 Day 2.9 Zr 1.3 Dad 0.4 Bi 0.3 O 12 -Co 0.05 Li 6.3 Day 2.9 Zr 1.3 Dad 0.4 Bi 0.3 O 12 -Co 0.1 Li 6.3 Day 2.9 Zr 1.3 Dad 0.4 Bi 0.3 O 12 -Co 0.15 Li 6.3 Day 2.9 Zr 1.3 Dad 0.4 Bi 0.3 O 12 -Co 0.2 Li 6.3 Day 2.93 Zr 1.3 Dad 0.4 Bi 0.3 O 12 -Co 0.05 Li 6.3 Day 2.93 Zr 1.3 Dad 0.4 Bi 0.3 O 12 -Co 0.1 Li 6.3 Day 2.93 Zr 1.3 Dad 0.4 Bi 0.3 O 12 -Co 0.15 Li 6.3 Day 2.95 Zr 1.3 Dad 0.4 Bi 0.3 O 12 -Co 0.05 Li 6.3 La 2.95 Zr 1.3 Ta 0.4 Bi 0.3 O 12 -Co 0.1 Li 6.3 La 2.95 Zr 1.3 Ta 0.4 Bi 0.3 O 12 -Co 0.15 Li 6.3 La 2.97 Zr 1.3 Ta 0.4 Bi 0.3 O 12 -Co 0.05 Li 6.3 La 2.97 Zr 1.3 Ta 0.4 Bi 0.3 O 12 -Co 0.1 Li 6.3 La 2.99 Zr 1.3 Ta 0.4 Bi 0.3 O 12 -Co 0.05 Li 6.3 La 2.99 Zr 1.3 Ta 0.4 Bi 0.3 O 12 -Co 0.1

[0043] The specific example of the chemical composition described above contains Co as a transition element, but Ni, Mn or Fe may be contained in place of Co.

[0044] [Method of manufacturing solid electrolyte ceramics] The solid electrolyte ceramics of the present invention can be obtained by mixing a compound containing a predetermined metal element (i.e., starting material) with water, drying, and then heat-treating. The compound containing the predetermined metal element is usually a mixture of compounds containing one metal element selected from the group consisting of Li (lithium), La (lanthanum), Bi (bismuth) and a predetermined transition metal element. Examples of the compound containing the predetermined metal element (i.e., starting material) include lithium hydroxide monohydrate LiOH·H2O, lanthanum hydroxide La(OH)3, zirconium oxide ZrO2, tantalum oxide Ta2O5, bismuth oxide Bi2O3, cobalt oxide Co3O4, basic nickel carbonate hydrate NiCO3·2Ni(OH)2·4H2O, manganese carbonate MnCO3, iron oxide Fe2O3, lithium nitrate LiNO3, lanthanum nitrate hexahydrate La(NO3)3·6H2O, and bismuth nitrate pentahydrate Bi(NO3)3·5H2O. The mixing ratio of the compounds containing the predetermined metal elements may be such that the solid electrolyte ceramic of the present invention has a predetermined chemical composition after heat treatment. The heat treatment temperature is usually 500°C to 1200°C, preferably 600°C to 1000°C. The heat treatment time is usually 10 minutes to 1440 minutes, particularly 60 minutes to 600 minutes.

[0045] The solid electrolyte ceramic of the present invention may contain a sintering aid. As the sintering aid, any sintering aid known in the field of solid-state batteries can be used. The composition of such a sintering aid preferably contains at least Li (lithium), B (boron), and O (oxygen), and the molar ratio of Li to B (Li / B) is preferably 2.0 or more. Specific examples of such sintering aids include, for example, Li3BO3, (Li 2.7 Al 0.3 )BO3, Li 2.8 (B 0.8 C 0.2 )O3, LiBO2.

[0046] The content of the sintering aid is usually preferably 0% or more and 10% or less, and particularly preferably 0% or more and 5% or less, based on the volume ratio of the garnet-type solid electrolyte.

[0047] [Solid battery] In the present specification, the term "solid-state battery" refers in a broad sense to a battery whose components (particularly the electrolyte layer) are made of solids, and in a narrow sense to an "all-solid-state battery" whose components (particularly all components) are made of solids. In the present specification, the term "solid-state battery" includes so-called "secondary batteries" that can be repeatedly charged and discharged, and "primary batteries" that can only be discharged. The "solid-state battery" is preferably a "secondary battery." The term "secondary battery" is not excessively limited by its name, and may also include electrochemical devices such as "electricity storage devices."

[0048] The solid-state battery of the present invention includes a positive electrode layer, a negative electrode layer, and a solid electrolyte layer, and usually has a laminated structure in which the positive electrode layer and the negative electrode layer are laminated with a solid electrolyte layer interposed therebetween. The positive electrode layer and the negative electrode layer may each be laminated in two or more layers as long as a solid electrolyte layer is provided between them. The solid electrolyte layer is in contact with the positive electrode layer and the negative electrode layer and is sandwiched between them. The positive electrode layer and the solid electrolyte layer may be integrally sintered as sintered bodies, and / or the negative electrode layer and the solid electrolyte layer may be integrally sintered as sintered bodies. The term "integrally sintered as sintered bodies" means that two or more adjacent or contacting members (particularly layers) are joined by sintering. Here, the two or more members (particularly layers) may be sintered as sintered bodies, but may be integrally sintered.

[0049] The above-mentioned solid electrolyte ceramics of the present invention are useful as a solid electrolyte for solid-state batteries. Therefore, the solid-state battery of the present invention contains the above-mentioned solid electrolyte ceramics of the present invention as a solid electrolyte. More specifically, the solid electrolyte ceramics of the present invention are contained as a solid electrolyte in at least one layer selected from the group consisting of a positive electrode layer, a negative electrode layer, and a solid electrolyte layer. From the viewpoint of more excellent ion conductivity in the solid electrolyte layer and more sufficient suppression of an increase in electronic conductivity during operation, it is preferable that the solid electrolyte ceramics of the present invention are contained at least in the solid electrolyte layer.

[0050] (Positive electrode layer) In the solid-state battery of the present invention, the positive electrode layer is not particularly limited. For example, the positive electrode layer may contain a positive electrode active material and may further contain the solid electrolyte ceramic of the present invention. By containing the solid electrolyte ceramic of the present invention in the positive electrode layer, it is possible to suppress short-circuiting of the solid-state battery. The positive electrode layer may have the form of a sintered body containing positive electrode active material particles. The positive electrode layer may be a layer capable of absorbing and releasing ions (particularly lithium ions).

[0051] The positive electrode active material is not particularly limited, and positive electrode active materials known in the field of solid-state batteries can be used. Examples of the positive electrode active material include lithium-containing phosphate compound particles having a Nasicon structure, lithium-containing phosphate compound particles having an olivine structure, lithium-containing layered oxide particles, and lithium-containing oxide particles having a spinel structure. Specific examples of lithium-containing phosphate compounds having a Nasicon structure that are preferably used include Li3V2(PO4)3, etc. Specific examples of lithium-containing phosphate compounds having an olivine structure that are preferably used include Li3Fe2(PO4)3, LiMnPO4, etc. Specific examples of lithium-containing layered oxide particles that are preferably used include LiCoO2, LiCo 1 / 3 Ni 1 / 3 Mn 1 / 3 Specific examples of lithium-containing oxides having a spinel structure that are preferably used include LiMn2O4, LiNi 0.5 Mn 1.5 O4, Li4Ti5O 12 From the viewpoint of reactivity during co-sintering with the LISICON-type solid electrolyte used in the present invention, LiCoO2, LiCo 1 / 3 Ni 1 / 3 Mn 1 / 3 It is more preferable to use a lithium-containing layered oxide such as O2. Only one type of these positive electrode active material particles may be used, or a mixture of two or more types may be used.

[0052] The positive electrode active material in the positive electrode layer has a Nasicon structure, which means that the positive electrode active material (particularly its particles) has a Nasicon crystal structure, and in a broader sense, means that the positive electrode active material has a crystal structure that can be recognized as a Nasicon crystal structure by those skilled in the art of solid-state batteries. In a narrower sense, the positive electrode active material in the positive electrode layer has a Nasicon structure, which means that the positive electrode active material (particularly its particles) shows one or more main peaks in X-ray diffraction at a specified incident angle, which correspond to Miller indices specific to the so-called Nasicon crystal structure. The compounds exemplified above are preferably used as positive electrode active materials having a Nasicon structure.

[0053] The positive electrode active material in the positive electrode layer has an olivine structure, which means that the positive electrode active material (particularly its particles) has an olivine crystal structure, and in a broad sense, means that the positive electrode active material has a crystal structure that can be recognized as an olivine crystal structure by those skilled in the art of solid-state batteries. In a narrow sense, the positive electrode active material in the positive electrode layer has an olivine structure, which means that the positive electrode active material (particularly its particles) shows one or more main peaks corresponding to Miller indices specific to the so-called olivine crystal structure at a predetermined incidence angle in X-ray diffraction. The above-mentioned compounds can be given as examples of the positive electrode active material having an olivine structure that is preferably used.

[0054] The positive electrode active material in the positive electrode layer has a spinel structure, which means that the positive electrode active material (particularly its particles) has a spinel crystal structure, and in a broad sense, means that the positive electrode active material has a crystal structure that can be recognized as a spinel crystal structure by a person skilled in the field of solid-state batteries. In a narrow sense, the positive electrode active material in the positive electrode layer has a spinel structure, which means that the positive electrode active material (particularly its particles) shows one or more main peaks corresponding to Miller indices specific to the so-called spinel crystal structure at a predetermined incidence angle in X-ray diffraction. The above-mentioned compounds can be given as examples of the positive electrode active material having a spinel structure that is preferably used.

[0055] The chemical composition of the positive electrode active material may be an average chemical composition. The average chemical composition of the positive electrode active material means the average value of the chemical composition of the positive electrode active material in the thickness direction of the positive electrode layer. The average chemical composition of the positive electrode active material can be analyzed and measured by breaking the solid-state battery and performing composition analysis by EDX (energy dispersive X-ray spectroscopy) in a field of view that includes the entire thickness direction of the positive electrode layer using SEM-EDX.

[0056] The positive electrode active material can be produced, for example, by the following method, or can be obtained as a commercial product. When producing the positive electrode active material, first, a raw material compound containing a predetermined metal atom is weighed so that the chemical composition is a predetermined chemical composition, and water is added and mixed to obtain a slurry. The slurry is then dried, calcined at 700°C to 1000°C for 1 hour to 30 hours, and pulverized to obtain the positive electrode active material.

[0057] The chemical composition and crystal structure of the positive electrode active material in the positive electrode layer may typically change due to elemental diffusion during sintering. The positive electrode active material may have the above-mentioned chemical composition and crystal structure in the solid-state battery after sintering with the negative electrode layer and the solid electrolyte layer.

[0058] The average particle size of the positive electrode active material is not particularly limited and may be, for example, 0.01 μm or more and 10 μm or less, and preferably 0.05 μm or more and 4 μm or less.

[0059] The average particle size (arithmetic mean) of the positive electrode active material can be determined, for example, by randomly selecting 10 to 100 particles from an SEM image and simply averaging their particle sizes. The particle diameter is the diameter of a spherical particle when the particle is assumed to be a perfect sphere. Such a particle diameter can be obtained, for example, by cutting out a cross section of a solid-state battery, taking a cross-sectional SEM image using a SEM, calculating the cross-sectional area S of the particle using image analysis software (for example, "A-zo-kun" (manufactured by Asahi Kasei Engineering Co., Ltd.)), and then calculating the particle diameter R using the following formula.

[0060]

number

[0061] The average particle size of the positive electrode active material in the positive electrode layer can be automatically measured by specifying the positive electrode active material by its composition when measuring the average chemical composition described above.

[0062] The average particle size of the positive electrode active material in the positive electrode layer may usually change due to sintering during the manufacturing process of the solid-state battery. The positive electrode active material may have the above-mentioned average particle size in the solid-state battery after sintering with the negative electrode layer and the solid electrolyte layer.

[0063] The volume ratio of the positive electrode active material in the positive electrode layer is not particularly limited, and may be, for example, 30% or more and 90% or less, and particularly 40% or more and 70% or less.

[0064] The positive electrode layer may contain the solid electrolyte ceramic of the present invention as a solid electrolyte, and / or may contain a solid electrolyte other than the solid electrolyte ceramic of the present invention. The positive electrode layer may further include a sintering aid and / or a conductive material.

[0065] When the positive electrode layer contains the solid electrolyte ceramic of the present invention, the volume ratio of the solid electrolyte ceramic of the present invention may usually be 20% or more and 60% or less, particularly 30% or more and 45% or less.

[0066] As the sintering aid in the positive electrode layer, compounds similar to the sintering aids that may be contained in the solid electrolyte ceramics can be used.

[0067] The volume ratio of the sintering aid in the positive electrode layer is not particularly limited, and is, for example, preferably from 0.1% to 20%, and more preferably from 1% to 10%.

[0068] The conductive material in the positive electrode layer can be a conductive material known in the field of solid-state batteries. Preferred conductive materials include metal materials such as Ag (silver), Au (gold), Pd (palladium), Pt (platinum), Cu (copper), Sn (tin), and Ni (nickel); and carbon materials such as acetylene black, Ketjen black, Super P (registered trademark), and carbon nanotubes such as VGCF (registered trademark). The shape of the carbon material is not particularly limited, and any shape such as spherical, plate, and fibrous may be used.

[0069] The volume ratio of the conductive material in the positive electrode layer is not particularly limited, and is, for example, preferably from 10% to 50%, and more preferably from 20% to 40%.

[0070] The thickness of the positive electrode layer is usually 0.1 to 30 μm, for example, preferably 1 to 20 μm. The thickness of the positive electrode layer is the average value of thicknesses measured at any 10 points in an SEM image.

[0071] In the positive electrode layer, the porosity is not particularly limited, but is preferably 20% or less, more preferably 15% or less, and further preferably 10% or less.

[0072] The porosity of the positive electrode layer was measured from an SEM image after FIB cross-section processing.

[0073] The positive electrode layer is a layer that may be called a “positive electrode active material layer.” The positive electrode layer may have a so-called positive electrode current collector or positive electrode current collector layer.

[0074] (Negative electrode layer) In the solid-state battery of the present invention, the negative electrode layer is not particularly limited. For example, the negative electrode layer may contain a negative electrode active material and may further contain the solid electrolyte ceramic of the present invention. By containing the solid electrolyte ceramic of the present invention in the negative electrode layer, it is possible to suppress short-circuiting of the solid-state battery. The negative electrode layer may have the form of a sintered body containing negative electrode active material particles. The negative electrode layer may be a layer capable of absorbing and releasing ions (particularly lithium ions).

[0075] The negative electrode active material is not particularly limited, and any negative electrode active material known in the field of solid-state batteries can be used. Examples of the negative electrode active material include carbon materials such as graphite, graphite-lithium compounds, lithium metal, lithium alloy particles, phosphoric acid compounds having a Nasicon structure, Li-containing oxides having a spinel structure, β II -Li3VO4 type structure, γ II The negative electrode active material is an oxide having a lithium metal, β II -Li3VO4 type structure, γ II It is preferable to use a Li-containing oxide having a -Li3VO4 type structure.

[0076] In the negative electrode layer, the oxide is β II -Li3VO4 type structure means that the oxide (particularly the particles) is β II -Li3VO4 type crystal structure, and in a broad sense, it is defined as a solid-state battery by those skilled in the art. II -Li3VO4 type crystal structure. In the narrow sense, the oxide in the negative electrode layer is β II The term "having a -Li3VO4 type structure" means that the oxide (particularly the particles) is a so-called β II It means that the β-Li3VO4 type crystal structure exhibits one or more major peaks corresponding to Miller indices specific to the β-Li3VO4 type crystal structure at a given incidence angle. II An example of the Li-containing oxide having a -Li3VO4 type structure is Li3VO4.

[0077] In the negative electrode layer, the oxide is γ II -Li3VO4 type structure means that the oxide (particularly the particles) is γ II -Li3VO4 type crystal structure, and in a broad sense, it is known by those skilled in the art of solid-state batteries as γ II In the narrow sense, the oxide in the negative electrode layer is γ IIThe term "having a -Li3VO4 type structure" means that the oxide (particularly the particles) is a so-called γ II - means that the crystal structure of Li3VO4 type shows one or more major peaks corresponding to Miller indices specific to the Li3VO4 type crystal structure at a given angle of incidence (x-axis). II As the Li-containing oxide having the Li-Li3VO4 type structure, Li 3.2 V 0.8 S 0.2 O4 is an example.

[0078] The chemical composition of the negative electrode active material may be an average chemical composition. The average chemical composition of the negative electrode active material means the average value of the chemical composition of the negative electrode active material in the thickness direction of the negative electrode layer. The average chemical composition of the negative electrode active material can be analyzed and measured by breaking the solid-state battery and performing composition analysis by EDX (energy dispersive X-ray spectroscopy) in a field of view that includes the entire thickness direction of the negative electrode layer using SEM-EDX.

[0079] The negative electrode active material can be produced, for example, by the same method as that for the positive electrode active material, or can be obtained as a commercially available product.

[0080] The chemical composition and crystal structure of the anode active material in the anode layer may usually be changed by elemental diffusion during sintering in the manufacturing process of the solid-state battery. The anode active material may have the average chemical composition and crystal structure described above in the solid-state battery after sintering with the cathode layer and the solid electrolyte layer.

[0081] The volume ratio of the negative electrode active material in the negative electrode layer is not particularly limited, and is, for example, preferably 50% or more (particularly 50% or more and 99% or less), more preferably 70% or more and 95% or less, and even more preferably 80% or more and 90% or less.

[0082] The negative electrode layer may contain the solid electrolyte ceramic of the present invention as a solid electrolyte, and / or may contain a solid electrolyte other than the solid electrolyte ceramic of the present invention. The negative electrode layer may further include a sintering aid and / or a conductive material.

[0083] When the negative electrode layer contains the solid electrolyte ceramic of the present invention, the volume ratio of the solid electrolyte ceramic of the present invention may usually be 20% or more and 60% or less, particularly 30% or more and 45% or less.

[0084] As the sintering aid in the negative electrode layer, the same compounds as the sintering aid in the positive electrode layer can be used. As the conductive material in the negative electrode layer, the same compounds as the conductive material in the positive electrode layer can be used.

[0085] The thickness of the negative electrode layer is usually 0.1 to 30 μm, and preferably 1 to 20 μm. The thickness of the negative electrode layer is determined by averaging thicknesses measured at any ten points in an SEM image.

[0086] In the negative electrode layer, the porosity is not particularly limited, but is preferably 20% or less, more preferably 15% or less, and further preferably 10% or less.

[0087] The porosity of the negative electrode layer is a value measured in the same manner as the porosity of the positive electrode layer.

[0088] The negative electrode layer is a layer that may be called a “negative electrode active material layer.” The negative electrode layer may have a so-called negative electrode current collector or negative electrode current collector layer.

[0089] (solid electrolyte layer) In the solid state battery of the present invention, the solid electrolyte layer preferably contains the above-mentioned solid electrolyte ceramic of the present invention from the viewpoints of superior ion conductivity and more sufficient suppression of an increase in electronic conductivity during operation.

[0090] The volume ratio of the solid electrolyte ceramic of the present invention in the solid electrolyte layer is not particularly limited, and from the viewpoint of better ion conductivity and more sufficient suppression of an increase in electronic conductivity during operation, it is preferably from 10% to 100%, more preferably from 20% to 100%, and even more preferably from 30% to 100%.

[0091] When the solid electrolyte layer contains the solid electrolyte ceramic of the present invention, it is sufficient that the solid electrolyte ceramic of the present invention having the above-mentioned chemical composition is present at least in the center of the thickness direction of the solid electrolyte layer (particularly at least 5 points, preferably at least 8 points, more preferably at least 10 points out of any 10 points). This is because the solid electrolyte layer is sandwiched between the positive electrode layer and the negative electrode layer, and element diffusion from the positive electrode layer and the negative electrode layer to the solid electrolyte layer and / or element diffusion from the solid electrolyte layer to the positive electrode layer and the negative electrode layer may occur due to sintering during the manufacturing process of the solid battery.

[0092] The solid electrolyte layer may contain, in addition to the garnet-type solid electrolyte ceramic of the present invention, one or more materials selected from a solid electrolyte composed of at least Li, Zr, and O, a solid electrolyte having a γ-Li3VO4 structure, and an oxide glass ceramic-based lithium ion conductor. An example of a solid electrolyte composed of at least Li, Zr, and O is Li2ZrO3.

[0093] An example of a solid electrolyte having a γ-Li3VO4 structure is a solid electrolyte having an average chemical composition represented by the following general formula (III).

[0094] [ka]

[0095] In formula (III), A is one or more elements selected from the group consisting of Na, K, Mg, Ca, Al, Ga, Zn, Fe, Cr, and Co. B is one or more elements selected from the group consisting of V and P. D is one or more elements selected from the group consisting of Zn, Al, Ga, Si, Ge, Sn, As, Ti, Mo, W, Fe, Cr, and Co. x satisfies 0≦x≦1.0, in particular 0≦x≦0.2. The value of y satisfies 0≦y≦1.0, and in particular 0.20≦y≦0.50. a is the average valence of A. The average valence of A is the value expressed as (n1×a+n2×b+n3×c) / (n1+n2+n3) when, for example, A contains n1 element X with a valence of a+, n2 element Y with a valence of b+, and n3 element Z with a valence of c+. c is the average valence of D. The average valence of D is the same as the average valence of A described above when, for example, n1 element X with a valence a+, n2 element Y with a valence b+, and n3 element Z with a valence c+ are recognized as D.

[0096] Specific examples of solid electrolytes having a γ-Li3VO4 structure include Li 3.2 (V 0.8 S 0.2 )O4, Li 3.5 (V 0.5 Ge 0.5 )O4, Li 3.4 (P 0.6 Si0.4)O4, Li 3.5 (P 0.5 Ge 0.5 )O4, etc.

[0097] As the oxide glass ceramic-based lithium ion conductor, for example, a phosphate compound containing lithium, aluminum, and titanium as constituent elements (LATP) or a phosphate compound containing lithium, aluminum, and germanium as constituent elements (LAGP) can be used.

[0098] The solid electrolyte layer may further contain, in addition to the solid electrolyte, for example, a sintering aid. As the sintering aid in the solid electrolyte layer, the same compounds as the sintering aid in the positive electrode layer can be used.

[0099] The volume proportion of the sintering aid in the solid electrolyte layer is not particularly limited, and from the viewpoint of better ion conductivity and more sufficient suppression of an increase in electronic conductivity during operation, it is preferably from 0% to 20%, and more preferably from 1% to 10%.

[0100] The thickness of the solid electrolyte layer is usually 0.1 to 30 μm, and preferably 1 to 20 μm from the viewpoint of better ion conductivity and more sufficient suppression of an increase in electronic conductivity during operation. The thickness of the solid electrolyte layer is the average value of thicknesses measured at any 10 points in an SEM image.

[0101] In the solid electrolyte layer, the porosity is not particularly limited, and from the viewpoint of better ion conductivity and more sufficient suppression of an increase in electronic conductivity during operation, it is preferably 20% or less, more preferably 15% or less, and even more preferably 10% or less.

[0102] The porosity of the solid electrolyte layer is a value measured in the same manner as the porosity of the positive electrode layer.

[0103] [Solid-state battery manufacturing method] The solid-state battery can be manufactured, for example, by the so-called green sheet method, the printing method or a combination of these methods.

[0104] The green sheet method will now be described. First, a paste is prepared by appropriately mixing a solvent, a binder, etc. with a positive electrode active material. The paste is applied onto a sheet and dried to form a first green sheet for forming a positive electrode layer. The first green sheet may contain a solid electrolyte, a conductive material, and / or a sintering aid, etc.

[0105] A paste is prepared by appropriately mixing the negative electrode active material with a solvent, a binder, etc. The paste is applied onto a sheet and dried to form a second green sheet for forming the negative electrode layer. The second green sheet may contain a solid electrolyte, a conductive material, and / or a sintering aid, etc.

[0106] A paste is prepared by appropriately mixing the solid electrolyte with a solvent, a binder, etc. The paste is applied and dried to prepare a third green sheet for forming the solid electrolyte layer. The third green sheet may contain a sintering aid, etc.

[0107] The solvent for producing the first to third green sheets is not particularly limited, and for example, a solvent that can be used in the manufacture of a positive electrode layer, a negative electrode layer, or a solid electrolyte layer in the field of solid state batteries is used. As the solvent, a solvent that can be used with the binder described below is usually used. As such a solvent, for example, alcohol such as 2-propanol is included.

[0108] The binder for producing the first to third green sheets is not particularly limited, and for example, a binder that can be used in the manufacture of a positive electrode layer, a negative electrode layer, or a solid electrolyte layer in the field of solid state batteries is used. Examples of such binders include butyral resin, acrylic resin, etc.

[0109] Next, the first to third green sheets are appropriately laminated to prepare a laminate. The laminate thus prepared may be pressed. A preferred pressing method is a hydrostatic pressing method. Thereafter, the laminate is sintered at, for example, 600 to 800° C. to obtain a solid-state battery.

[0110] The printing method will be explained. The printing method is similar to the green sheet method, except for the following: Prepare ink for each layer having the same composition as the paste for each layer used to obtain the green sheet, except that the amounts of solvent and resin are suitable for use as an ink. · Each layer is printed using ink and laminated to create a laminate.

[0111] The present invention will be described in more detail below based on specific examples. However, the present invention is not limited to the following examples and can be modified as appropriate within the scope of the present invention. EXAMPLES

[0112] <Examples 1 to 26 and Comparative Examples 1 to 10> [Production of solid electrolyte ceramics] The raw materials used were lithium hydroxide monohydrate (LiOH·H2O), lanthanum hydroxide (La(OH)3), zirconium oxide (ZrO2), tantalum oxide (Ta2O5), bismuth oxide (Bi2O3), cobalt oxide (Co3O4), basic nickel carbonate hydrate (NiCO3·2Ni(OH)2·4H2O), manganese carbonate (MnCO3), and iron oxide (Fe2O3). Each starting material was weighed so as to have the chemical composition shown in Table 1. Water was added, the mixture was placed in a polyethylene pot, and the pot was rotated at 150 rpm for 16 hours to mix the raw materials. In addition, lithium hydroxide monohydrate (LiOH·H2O), the Li source, was charged in an amount 3 wt% in excess of the target composition, taking into account Li deficiency during sintering. The obtained slurry was evaporated and dried, and then calcined in O2 at 900°C for 5 hours to obtain the target phase. A mixed solvent of toluene and acetone was added to the calcined powder and pulverized in a planetary ball mill for 12 hours. The pulverized powder was confirmed to have no compositional deviation by ICP measurement. The average particle size of the pulverized powder was 150 nm.

[0113] [Manufacturing of solid electrolyte single plate] As an evaluation sample of the solid electrolyte ceramics, a solid electrolyte single plate was produced by the following method.

[0114] The obtained solid electrolyte powder, butyral resin, and alcohol were thoroughly mixed in a weight ratio of 200:15:140, and then the alcohol was removed on a hot plate at 80° C. to obtain a powder coated with butyral resin as a binder. The coated powder was then pressed at 90 MPa using a tablet press to form tablets. The tablet was thoroughly covered with mother powder and degreased at 500°C in an oxygen atmosphere to remove the butyral resin. It was then sintered at approximately 1200°C for 3 hours in an oxygen atmosphere and cooled to room temperature to obtain a sintered solid electrolyte. The surface of the obtained sintered body was polished to obtain a garnet solid electrolyte single plate.

[0115] [Crystal structure of solid electrolyte single plate] In all of the Examples and Comparative Examples, it was confirmed that X-ray diffraction patterns attributable to a crystal structure similar to that of a garnet type were obtained by X-ray diffraction of the solid electrolyte single plate (ICDD Card No. 00-045-0109).

[0116] [Chemical composition of solid electrolyte plate] The solid electrolyte single plate was subjected to ICP analysis to obtain the average chemical composition of the solid electrolyte single plate. The La content and the Co, Mn, Ni and Fe contents in the average chemical composition of the entire solid electrolyte single plate were calculated based on the number of 6-coordinated sites in the garnet-type crystal structure (for example, Bi and D in the above general formula (II)). 1 The ratio was calculated based on the total number of A, B, and D in the chemical composition (the sum of the elements A, B, and D) taken as 100 mol %. Note that the O (oxygen) in the chemical composition is a value calculated so as to achieve charge neutrality based on the molar ratio and valence of the elements A, B, and D in the general formula (I).

[0117] [Electronic conductivity measurement] An Au electrode was sputtered onto one side of the obtained single plate to make it the working electrode. Li metal with the same area as the Au electrode was attached to the other side. Finally, the cell was sealed in a 2035 size coin cell to make it the evaluation cell. All of the above operations were carried out in a dry room with a dew point of -40°C or less. A voltage of 2 V was applied to the working electrode relative to Li at room temperature, and the transient current was observed. The current that flowed 10 hours after the voltage application was read as the leakage current. The electronic conductivity was calculated from the leakage current using the following formula. Electronic conductivity = (I / V) x (L / A) (I: leakage current, V: applied voltage, L: solid electrolyte plate thickness, A: electrode area) ◎: Electronic conductivity <1.0×10 -8 S / cm(excellent); ○;1.0×10 -8 S / cm≦Electronic conductivity<5.0×10 -8 S / cm(good); △;5.0×10 -8 S / cm≦Electronic conductivity<1.0×10 -7 S / cm (Acceptable) (No problem in practical use); ×;1.0×10 -7 S / cm ≦ Electronic conductivity (unacceptable) (problems in practical use).

[0118] [Ionic conductivity measurement] A gold (Au) layer was formed on both sides of the solid electrolyte plate as a current collector by sputtering, and then the plate was sandwiched and fixed between SUS current collectors. The sintered tablets of each solid electrolyte were subjected to AC impedance measurement at room temperature (25°C) in the range of 10 MHz to 0.1 Hz (±50 mV) to evaluate the ionic conductivity. ◎: 1.3×10 -3 S / cm ≤ ionic conductivity (excellent); ○;1.0×10 -3 S / cm≦Ionic conductivity<1.3×10 -3 S / cm(good); △;5.0×10 -4 S / cm≦Ionic conductivity<1.0×10 -3 S / cm (Acceptable) (No problem in practical use); ×; ionic conductivity < 5.0 × 10-4 S / cm (not possible) (problems in practical use).

[0119] [Overall Judgment] All the evaluation results of electronic conductivity and ionic conductivity were evaluated comprehensively. ⊚: All the evaluation results of electronic conductivity and ionic conductivity were ⊚. ◯: The lowest evaluation result of all the evaluation results of electronic conductivity and ionic conductivity was ◯. Δ: The lowest evaluation result among all evaluation results of electronic conductivity and ionic conductivity was Δ. ×: The lowest evaluation result of all the evaluation results of electronic conductivity and ionic conductivity was ×.

[0120] [Table 1]

[0121] [Table 2]

[0122] From a comparison between Comparative Examples 1 and 2 and Examples 1 to 12, it is clear that when the La content is less than 132.0 mol %, the ionic conductivity decreases. A comparison between Examples 1 to 12 and Comparative Examples 3 to 5 reveals that when the La content is in the range of 132.0 mol% or more and 145.0 mol% or less, when the content of a specific transition metal element (particularly Co) is greater than 12.0 mol%, the electronic conductivity becomes high and the risk of a short circuit increases. A comparison of Examples 13 to 18 with Comparative Examples 6 and 7 reveals that in the range where the La content is more than 145.0 mol% and not more than 147.5 mol%, when the content of a specific transition metal element (particularly Co) is greater than 9.0 mol%, the electronic conductivity becomes high and the risk of a short circuit increases. A comparison of Examples 19 to 22 with Comparative Examples 8 and 9 reveals that when the La content is in the range of more than 147.5 mol% and less than 150.0 mol%, if the content of a specific transition metal element (especially Co) is greater than 6.0 mol%, the electronic conductivity becomes high and the risk of a short circuit increases. From a comparison between Examples 19 to 22 and Comparative Example 10, it is clear that when the La content is 150.0 mol % or more, the electronic conductivity increases, increasing the risk of short circuit. [Industrial Applicability]

[0123] A solid-state battery including the solid electrolyte ceramic of the present invention can be used in various fields where battery use or power storage is expected. By way of example only, a solid-state battery according to an embodiment of the present invention can be used in the field of electronics packaging. The solid-state battery according to an embodiment of the present invention can also be used in the electrical, information, and communication fields where mobile devices and the like are used (e.g., electrical and electronic devices fields including small electronic devices such as mobile phones, smartphones, smart watches, notebook computers, digital cameras, activity meters, arm computers, electronic paper, wearable devices, RFID tags, card-type electronic money, and smart watches, or mobile device fields), household and small industrial applications (e.g., power tools, golf carts, household, nursing care, and industrial robots), large industrial applications (e.g., forklifts, elevators, and port cranes), transportation systems (e.g., hybrid cars, electric cars, buses, trains, electrically assisted bicycles, and electric motorcycles), power system applications (e.g., various power generation, road conditioners, smart grids, and general household storage systems), medical applications (medical devices such as earphones and hearing aids), pharmaceutical applications (medical management systems), IoT, and space and deep sea applications (e.g., space probes, submersible research vessels, and the like).

Claims

1. The alloy contains at least Li (lithium), La (lanthanum), Bi (bismuth) and O (oxygen), and further contains one or more transition metal elements selected from the group consisting of Co (cobalt), Ni (nickel), Mn (manganese) and Fe (iron); The following general formula (I): 【Chemistry 1】 (In formula (I), A is one or more elements selected from the group consisting of Li (lithium), Ga (gallium), Al (aluminum), Mg (magnesium), Zn (zinc) and Sc (scandium), and includes at least Li (lithium); B is one or more elements selected from the group consisting of La (lanthanum), Ca (calcium), Sr (strontium), Ba (barium), and lanthanoid elements, including at least La (lanthanum); D is one or more elements selected from the group consisting of transition elements capable of forming 6-coordination with oxygen and typical elements belonging to groups 12 to 15, and includes at least Bi (bismuth); α satisfies 5.0≦α≦8.0; β satisfies 2.5≦β≦3.5; γ satisfies 1.5≦γ≦2.5; (ω satisfies 11≦ω≦13) The chemical composition is represented by A solid electrolyte ceramic having a garnet-type crystal structure, which satisfies any one of the following relational expressions (1) to (3) when the content of D is 100 mol %, the content of La is X (mol %), and the total content of the one or more transition metal elements is Y (mol %): (1) In the range of 147.5<X<150.0, 0.01≦Y≦6.0; (2) 145.0<X≦147.5 and 0.01≦Y≦9.0; (3) In the range of 132.0≦X≦145.0, 0.03≦Y≦12.

0.

2. The solid electrolyte ceramic according to claim 1 , wherein the solid electrolyte ceramic satisfies the relational expression (1) or (2).

3. The solid electrolyte ceramic according to claim 1 or 2, which satisfies the relational expression (1).

4. The solid electrolyte ceramic according to any one of claims 1 to 3, wherein the one or more transition metal elements include Co.

5. A solid-state battery comprising the solid electrolyte ceramic according to any one of claims 1 to 4.

6. the solid-state battery includes a positive electrode layer, a negative electrode layer, and a solid electrolyte layer laminated between the positive electrode layer and the negative electrode layer, The solid-state battery according to claim 5 , wherein the positive electrode layer and the negative electrode layer are layers capable of absorbing and releasing lithium ions.

7. The solid-state battery according to claim 6 , wherein the solid electrolyte layer is integrally sintered with the positive electrode layer and the negative electrode layer.

8. The solid-state battery according to any one of claims 5 to 7, wherein the solid electrolyte ceramic is contained in a solid electrolyte layer of the solid-state battery.

Citation Information

Patent Citations

  • Material for solid electrolyte

    JP2014170734A

  • Solid electrolyte ceramics material

    JP2015050071A

  • Stabilizing Coatings for Solid-State Batteries

    JP2019530963A

  • Mixed ionic and electronic conductors for solid-state batteries

    JP2020530188A